2021
DOI: 10.3389/fphar.2020.585821
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 and SIRT2 Activity Control in Neurodegenerative Diseases

Abstract: Sirtuins are NAD+ dependent histone deacetylases (HDAC) that play a pivotal role in neuroprotection and cellular senescence. SIRT1-7 are different homologs from sirtuins. They play a prominent role in many aspects of physiology and regulate crucial proteins. Modulation of sirtuins can thus be utilized as a therapeutic target for metabolic disorders. Neurological diseases have distinct clinical manifestations but are mainly age-associated and due to loss of protein homeostasis. Sirtuins mediate several life ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 269 publications
(339 reference statements)
1
81
0
Order By: Relevance
“…A recent study has also demonstrated the highly beneficial role SIRT1 plays in the brain, protecting against neurological disorders and cerebral ischemia (Xu et al, 2018). It was found that SIRT1 is expressed at low levels in the brains of patients with AD, where it acts to deacetylate AD-affected neurons causing repression of p53 and inhibition of apoptosis (Manjula et al, 2020). The levels of SIRT1 were also highly correlated to Braak stage, a system used to determine the severity of dysfunction in neurological pathologies (Burke et al, 2008;Manjula et al, 2020).…”
Section: Mir-34amentioning
confidence: 97%
See 1 more Smart Citation
“…A recent study has also demonstrated the highly beneficial role SIRT1 plays in the brain, protecting against neurological disorders and cerebral ischemia (Xu et al, 2018). It was found that SIRT1 is expressed at low levels in the brains of patients with AD, where it acts to deacetylate AD-affected neurons causing repression of p53 and inhibition of apoptosis (Manjula et al, 2020). The levels of SIRT1 were also highly correlated to Braak stage, a system used to determine the severity of dysfunction in neurological pathologies (Burke et al, 2008;Manjula et al, 2020).…”
Section: Mir-34amentioning
confidence: 97%
“…It was found that SIRT1 is expressed at low levels in the brains of patients with AD, where it acts to deacetylate AD-affected neurons causing repression of p53 and inhibition of apoptosis (Manjula et al, 2020). The levels of SIRT1 were also highly correlated to Braak stage, a system used to determine the severity of dysfunction in neurological pathologies (Burke et al, 2008;Manjula et al, 2020). Further, elevated levels of SIRT1 were shown to provide protection against the development of Huntington's Disease 30532738 (Xu et al, 2018).…”
Section: Mir-34amentioning
confidence: 99%
“…A study has also been found that overactivation of PARP1 can also trigger the defect of mitochondrial autophagy by inhibiting the NAD+-SIRT1-PGC-1α pathway, which is related to the regulation of mitochondrial autophagy by SIRT1 through a variety of pathways, and this can be partially normalized with PARP1 inhibitors or pharmacological interventions with compounds that increase NAD+ abundance (Fang et al, 2014 ). There is also evidence that toxic proteins associated with neurodegenerative diseases can also reduce the expression of SIRT1, or directly interact with SIRT1 protein to inhibit its affinity with substrates and increase the acetylation of their substrates (Jiang et al, 2011 ; Manjula et al, 2020 ). Such as the expression of SIRT1 protein in the parietal cortex of patients with AD is significantly decreased and is closely related to the accumulation of Aβ and tau proteins (Kerr et al, 2017 ).…”
Section: Expression and Activity Of Sirt1 Decreased In Aging Neurodegenerative And Metabolic Diseasesmentioning
confidence: 99%
“…Sirtuins catalyze the deacetylation of target proteins by converting NAD+ into NAM and a O-Acyl ATP ribose. The activity of SIRTs has been profusely studied in the nucleus, where they control the function of different transcription factors and histone proteins to regulate cell senescence and neurodegeneration [101,102]. In addition, PARPs are enzymes that normally control DNA repair, whose overactivation under intense DNA oxidative damage may lead to cellular depletion of NAD+ and ATP.…”
Section: The Role Of Nadh In Cell Metabolism and Antioxidant Defensementioning
confidence: 99%